2012
DOI: 10.1016/j.critrevonc.2011.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Vaginal cancer

Abstract: Because of the low incidence of vaginal cancer, phase III trials have not been carried out and current guidelines have been drawn on retrospective studies. This state of affairs explains the variety of treatments to which women affected by this disease are subjected to. In this article, we report the current results achieved by different therapeutic strategies. The primary treatment options in Stage I vaginal carcinoma are surgery and/or radiotherapy. For a small tumor, a wide excision can be used. For high ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 48 publications
0
54
0
4
Order By: Relevance
“…Total tumor dose as a continuous parameter and technique of therapy (EBRT alone and EBRT + intracavitary RT) were significant prognostic factors by univariate analysis (p < 0.05). A review of literature on 17 studies showed a cumulative 5-year survival ranging from 0% to 80% for patients with FIGO stage III vaginal carcinoma treated with RT alone [23]. Combination of EBRT and BT was the most commonly used treatment in this clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Total tumor dose as a continuous parameter and technique of therapy (EBRT alone and EBRT + intracavitary RT) were significant prognostic factors by univariate analysis (p < 0.05). A review of literature on 17 studies showed a cumulative 5-year survival ranging from 0% to 80% for patients with FIGO stage III vaginal carcinoma treated with RT alone [23]. Combination of EBRT and BT was the most commonly used treatment in this clinical setting.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the anatomy of the region and the close proximity of the vagina to critical pelvic structures such as the bladder, urethra and rectum, surgery has a limited role in the management of vaginal carcinoma [1,6,[42][43][44][45][46][47]. The standard treatment is radiotherapy, which utilizes external beam radiation [EBRT] and/or brachytherapy [BT] techniques [6,22,[48][49][50][51][52][53][54][55][56][57][58][59][60][61].…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Nowadays, surgery can be taken into consideration in accurately selected cases of: (i) stage I disease confined to the upper posterior vagina; (ii) stage IV disease with recto-vaginal or vesico-vaginal fistula; (iii) central recurrence after radiotherapy [1,6,42,44,45,47,[69][70][71]. As far as the patients with stage I disease are concerned, surgery consists of radical hysterectomy, upper vaginectomy and pelvic lymphadenectomy if the uterus is still in situ, and radical upper vaginectomy and pelvic lymphadenectomy if the uterus has been previously removed.…”
Section: Surgerymentioning
confidence: 99%
“…Brachytherapy is essential for management of primary vaginal cancer where radical surgery is often precluded by significant morbidity [1,2]. Patients with vaginal recurrence of pelvic tumors such as endometrial cancer are infrequently candidates for repeat surgical excision [3], however combination BT and EBRT provides excellent long-term control and is a potentially curative option in localized disease [4,5,6].…”
Section: Purposementioning
confidence: 99%